Religiosity and Student Character Formation in Vocational Education: A Mediated Model of Motivation and Literacy in Indonesia - Hesti Winingsih; Fajri Ismail; Karoma Karoma; Indah Wigati; Maryamah Maryamah; M. Kharis Fadillah; Wildan Miftahussurur (LP. Ma'arif Janggan Magetan, 2024)
This study examines the role of religiosity in student character formation within vocational education by analyzing the mediating effects of learning motivation and literacy. Employing a quantitative correlational design with an ex post facto approach, the study analyzes survey data collected from 381 students enrolled in public vocational secondary schools in Indonesia (N = 381). Religiosity is conceptualized as a multidimensional construct encompassing belief, practice, experience, and social consequences, while student character is defined as an integrated set of cognitive, moral, and socio-emotional dispositions. Data were analyzed using regression-based mediation analysis within a structural equation modeling framework, indicating that religiosity has a positive and statistically significant direct effect on student character. In addition, learning motivation and literacy function as significant mediating variables, demonstrating partial mediation in the relationship between religiosity and character formation. These findings suggest that religious values influence character development not only through direct moral orientation, but also indirectly by strengthening students’ motivational engagement and interpretive capacities. By empirically testing a mediated model of character formation, this study advances a mechanism-oriented understanding of how values, motivation, and literacy interact in vocational education. The findings contribute theoretically to research on character education and religious education, while practically underscoring the importance of integrating ethical values, motivational support, and literacy development in holistic vocational education models.